Coercive agency in mission education at Lovedale Missionary Institution - Duncan, Graham (HTS teologiese studies, 2004)
Any society and its institutions are coercive. While acknowledging the invaluable contribution made by mission education towards the development of black South Africans, Lovedale Missionary Institution exemplifies the concept of a “total institution” susceptible to the problems of power relations. Those who studied there internalized its ethos. Coercive agency encouraged adaptation to missionary ideology. However, many Lovedale students rejected the mores of the religion and education they received as they challenged and resisted the effects of the coercive agency of internalization. Institutionalisation is, by nature, resistant to change as can be seen in the policies of the respective Principals of the Institution. Consequently, black people were alienated by a process of “exclusion”. The values of justice, love and peace are appropriate tools for a new model of education in South Africa.